2007
DOI: 10.17705/1jais.00136
|View full text |Cite
|
Sign up to set email alerts
|

From Prediction to Explanation: Reconceptualizing and Extending the Perceived Characteristics of Innovating

Abstract: Individual adoption and use of technology remains a critical concern for both managers and professionals. Despite the widespread integration of technology into work and organizations, there remain many opportunities for individuals to either extend or limit their use of IT at work. This paper extends work on the Perceived Characteristics of Innovating (PCI), as defined by Moore and Benbasat in 1991. Building on studies over the past ten years as well as on additional empirical research, we provide two contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 59 publications
(101 reference statements)
2
19
0
2
Order By: Relevance
“…Te results also confrm a positive efect of social network in the context of ADVs, congruent with the fndings of Higgins et al [67] and Min et al [60]. Once one person starts using ADVs, more and more of their friends and family also begin to use ADVs, with such use difusing along their social networks.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Te results also confrm a positive efect of social network in the context of ADVs, congruent with the fndings of Higgins et al [67] and Min et al [60]. Once one person starts using ADVs, more and more of their friends and family also begin to use ADVs, with such use difusing along their social networks.…”
Section: Discussionsupporting
confidence: 83%
“…In other words, people will consciously imitate behaviors as exhibited in their social network. Consistent with Higgins et al [67], Min et al [60] also found that social infuence had a positive efect on the acceptance of a new technology. Social infuence is also considered in this study in order to explore the positive feedback and recommendations communicated between members of close social groups as they relate to intentions toward ADV adoption.…”
Section: Constructs In the Conceptualsupporting
confidence: 64%
“…1). The theoretical underpinnings of this model stem from the stimuli-organism-response (SOR) model (Meharbian and Russell 1974;Holak and Lehmann 1990;Higgins et al 2007). The S-O-R model assumes that an organism exposed to psychological or environmental stimuli will process these stimuli personally and respond accordingly (Arora 1982;Slama and Tashchian 1987).…”
Section: Study Design and Datamentioning
confidence: 99%
“…Voluntary use occurs when teams have the option to decide to use the technology or not (Leonard-Barton & Deschamps, 1988). Conceptually, voluntary use of AI is hypothesized to influence behavior directly (e.g., Chen et al, 2015; Hester, 2011; Higgins et al, 2007) and also indirectly (Belanche et al, 2019). However, empirical findings regarding the voluntary use of AI remain inconsistent, yielding positive, negative, and no support for most of the hypothesized relationships (e.g., Hester, 2011; Higgins et al, 2007; Hsu et al, 2007; Templeton & Byrd, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%